Exploring a decade of maritime transportation studies: Trends and developments - Wulandari, Retno Sawitri; Cahyadi, Tri; Winarno, Winarno; Harianto, B.B (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to identify trends and developments in maritime transportation research over the past decade using bibliometric analysis based on Scopus data. Bibliographic coupling and co-word analysis techniques were employed to evaluate research relationships, topic trends, and their impact. VOSviewer software was utilized to map the research network. The bibliometric coupling analysis revealed four major clusters, including sustainability strategies, operational optimization, digital transformation, and navigation safety. Meanwhile, the co-word analysis identified three dominant themes: maritime accident prediction, China’s container trade growth, and sustainable maritime transportation strategies. Research trends indicate an increasing focus on digital technologies, such as artificial intelligence and the Internet of Things (IoT), in navigation and port management. Theoretically, this study enhances the understanding of the knowledge structure in maritime transportation. Practically, the findings provide valuable insights for industry stakeholders and policymakers in developing evidence-based strategies to improve the efficiency, sustainability, and safety of maritime transportation.